(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
In this study, We produce the new numerical scheme which relies on sextic B-spline Galerkin method takes with quintic B-spline as a weight function, for solving the Burger’s equation, contrasted with exact solution can be done and then we find out a linear stability analysis which is erect on a Fourier (Von Neumann) method.